Pengaruh Kesehatan Mental terhadap Prestasi Akademik Mahasiswa - Gendis Gayatri; Diva Nur Azizah; Aldisha Adya Pasha; Sri Mulyeni (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2026)
Mental health is a very important element in supporting students' academic success. As a group at a vulnerable age, students often face academic, social, and psychological pressures that can affect their mental health and academic performance. This study aims to examine the impact of mental health on the academic performance of students at the Faculty of Economics, Pasim National University. The method used in this study is a quantitative approach with data collection through questionnaires. The research subjects consisted of 123 students in their first semester, where the sample included 94 respondents selected using the Slovin formula. The data were analyzed using SPSS software, including validity, reliability, and normality tests, simple linear regression, coefficient of determination, and ANOVA. The findings of this study indicate that all measurement tools used are valid and reliable. Normality testing shows that the data have a normal distribution. The regression analysis results showed a significant positive effect of mental health on students' academic performance. An R-squared value of 0.410 indicates that mental health contributes 41% to the variation in students' academic results, while the remaining 59% is influenced by other factors. The results of the ANOVA also showed a significance level of 0.000 (<0,05). confirming the suitability of the regression model. Therefore, it can be concluded that mental health plays a significant role in improving student academic achievement. This research is expected to provide educational institutions with a basis for designing mental health support policies and programs to improve student academic quality.